Difficulties of Undergraduate English Education Students on Reading Comprehension - Parjer, Mutiara Savitri; Ghozali, Imam; Basya, Dihliza (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
The researcher could analyse the student difficulties on reading comprehension of in advance level of English. The aim of this study is to explore student’s accounts and experiences to find difficulties which related to perceptions and experiences. The data gathered by interview and by in depth analysing showed that the difficulties were around improving knowledge content, building vocabulary, phrase, pronunciation, and getting the meaning or texts to contexts. There were various aspects influence this situation; the meaning of word of sentence, background knowledge, academic vocabulary, and finding of topic on text.